Comparison of Different Analytical Methods for the Determination of Carbon Monoxide in Postmortem Blood. Issue 2 (1st October 2019) - Zanaboni, Moira; Roda, Gabriella; Arnoldi, Sebastiano; Casagni, Eleonora; Gambaro, Veniero; Dei Cas, Michele
Abstract: The determination of carbon monoxide (CO) and carboxyhemoglobin (COHb) is of utmost importance in forensic toxicology to determine the cause of death in cases of CO poisoning, fire, and explosions. To this end, reliable and updated analytical methods are required. In this paper, four different methods for the determination of carbon monoxide in postmortem blood samples were compared: (i) the spectrophotometric determination of COHb applying the method proposed by Rodkey and modified by Beutler–West, (ii) the spectrophotometric determination of CO using a micro‐diffusion‐based method, (iii) the determination of CO by gas chromatography coupled to a TCD detector, and (iv) the determination of COHb by blood gas analysis. Three postmortem blood samples were analyzed with all methods, and the results were comparable. The applied methodologies showed different features depending on the sensitivity, sample preparation, and volume. The HS‐GC/TCD method in our hand was the most appropriate, on postmortem samples, and versatile to apply. Unfortunately, only a limited number of postmortem blood samples were available for this study due to the rarity of that kind of intoxication in our jurisdiction.